2021
DOI: 10.1007/s13181-021-00847-2
|View full text |Cite
|
Sign up to set email alerts
|

Truncal Ataxia and Prolonged Coma in an Exploratory Pediatric Perampanel Ingestion

Abstract: Introduction Several overdoses of the antiepileptic drug perampanel have been reported in adults, but very few have been reported in children. We report the case of an observed exploratory ingestion of perampanel in a 2-year-old child that resulted in ataxia and prolonged coma. Case Report A previously healthy 2-year-old female patient presented to the emergency department (ED) 30 minutes after the witnessed ingestion of 30 mg of perampanel (2 mg/kg). Within minutes of ingestion, she displayed ataxia and inabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…[24][25][26] Although there was no considerable difference in terms of pharmacology, pediatric patients did differ from adult patients in some aspects, particularly with respect to drug sensitivity and toxicity. [16,27,28] Second, several studies have normalized dosage increases every 1 to 3 weeks under the guidance of a target dose (12 mg/day), [27,29] and some patients had dose adjustments only after 4 to 8 weeks. [2] Nevertheless, perampanel was up-titrated on a more frequent schedule for patients who had inadequately controlled seizures than the prespecified schedule (every 1-2 weeks).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] Although there was no considerable difference in terms of pharmacology, pediatric patients did differ from adult patients in some aspects, particularly with respect to drug sensitivity and toxicity. [16,27,28] Second, several studies have normalized dosage increases every 1 to 3 weeks under the guidance of a target dose (12 mg/day), [27,29] and some patients had dose adjustments only after 4 to 8 weeks. [2] Nevertheless, perampanel was up-titrated on a more frequent schedule for patients who had inadequately controlled seizures than the prespecified schedule (every 1-2 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 , 14 ] Currently, most studies on pediatric patients have focused on patients who were >12 years of age. However, dose-related toxicity has been reported in patients aged ≤2 years who received perampanel [ 15 , 16 ] ; hence, it is important to assess the safety and tolerability of treatment protocols in younger pediatric patients with epilepsy. This study reported the effectiveness and tolerability of perampanel in pediatric patients ≤12 years of age with refractory epilepsy.…”
Section: Introductionmentioning
confidence: 99%